In Situ High-Temperature Synchrotron X-ray Studies of Microstructure and Phase Composition of Additively Fabricated Ti–6Al–4V/TiC Metal Matrix Composite; Journal of Surface Investigation: X-ray, Synchrotron and Neutron Techniques; Vol. 19, iss. 4 - Panin A. V. Alexey Viktorovich; Syrtanov M. S. Maksim Sergeevich; Lobova T. A. Tatjyana Anatoljevna; Perevalova O. B. Olga Borisovna; Kazachenok M. S. Marina Sergeevna (2025, 2025)
The microstructure and phase composition of Ti–6Al–4V/TiC metal matrix composite samples obtained by wire-feed electron-beam additive manufacturing are investigated by X-ray diffraction analysis and optical, scanning, and transmission electron microscopy. It is shown that the microstructure of the Ti–6Al–4V/TiC composite consists of primary β-grains containing α/α′-plates separated by interlayers of residual β- and α′′-phases. Irregularly shaped TiC carbide particles with sizes of 1–2 µm are distributed along the boundaries of the primary β-grains. The changes in the phase composition of the 3D-printed Ti–6Al–4V/TiC composites during heating from room temperature to 1100°C are investigated by X-ray diffraction using synchrotron radiation. The changes in the shape and position of the X-ray peaks of α/α′- and β-phases during heating and cooling are analyzed. It is shown that in the temperature range of 700–800°C, there is a shift of the 110 peak of the β-phase towards large angles, as well as a change in its full width at half maximum associated with the formation and subsequent decomposition of the orthorhombic α′′-phase